Eco-innovation in the transition to a circular economy: An analytical literature review. (20th January 2018) - de Jesus, Ana; Antunes, Paula; Santos, Rui; Mendonça, Sandro
Abstract: In the ongoing sustainability debate, the circular economy (CE) has been steadily gaining ground as a new paradigm. At the same time, eco-innovation (EI) has been recognised as a key element in carrying out the transition from a linear to a circular system of production and consumption. However, little information can be found concerning whether and how EI can actually facilitate the change to a CE. While extensive literature on EI, and a growing body of research exploring the CE, already exist, there is, as yet, no comprehensive understanding concerning the connections between these two concepts. Drawing on academic contributions from the fields of EI and CE, this analysis seeks to clarify and synthesise findings at the intersection of these two fields. The aim is threefold: derive literature-based working definitions of CE and EI; review the role of EI at CE's macro, meso, and micro levels; and characterise CE-inducing EI in terms of targets, mechanisms and impacts. Our literature review shows that an EI-driven techno-economic transition to a CE requires specific solutions, i.e. different forms of EI-driven "clean congruence" at distinct levels of operation. Generally speaking, movement toward a CE is found to be contingent on "systemic" EI, that is, not only intense in technology but also involving dynamic and holistic combinations of service innovations and novel organisational set-ups. Highlights: Transition towards sustainability and new techno-economic paradigms. Circular economy (CE) as a new set-up to replace the old industrial model. Eco-innovation (EI) as a way to operationalise the changes required by CE. The interactions between EI and CE are specified. Circularity contingent on systemic/transformative EI.